Marketing Strategies In Increasing BRILINK Income (Case Study in Sukarme Baru Village, Sukarame Subdistrict) Bandar Lampung City): Strategi Pemasaran Dalam Meningkatkan Pendapatan BRILink (Studi Kasus di Kelurahan Sukarme Baru, Kecamatan Sukarame) Kota Bandar Lampung) - Andi Surya; M. Renandi Ekatama; Chandra Andestya Pratama AK (Institute of Educational, Research, and Community Service, 2023)
This study aims to: (1) find out what things need to be considered and carried out as a BRILink Agent. (2) knowing BRILink's marketing strategy to increase revenue. In writing this final assignment, the author made direct observations on BRILink agents. Data was obtained by conducting interviews with BRILink Agents. The results of the study show that: (1) provide special services to people who have not been served administratively by banks. (2) In increasing the income of BRILink Agents apply a mix of marketing strategies, namely product, price, place, promotion.